The role of copper and cobalt in animal nutrition with special reference to the utilisation of their alkali-soluble complexes - Van der Merwe, F. J.(Francois Johannes),1932- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1954.